An Analysis of Students’ Speaking Ability on Specific Purpose of Learning - ilham ilham; Muhammad Fauzi Bafadal; Muslimin Muslimin (Linguistics and ELT Journal, 2019)
ABSTRACTThe objectives of this research were to find out the students’ speaking English ability on specific purpose of learning in academic year 2018/2019. This research focus on the specific material in learning at the second semester students’ of Planology Study Program in academic year 2018/2019This research used a descriptive quantitative research. The total number of population of this research was 50 students. The researcher took the sample by using a purposive sampling. Thus, the total number of sample was 20 students. In data collection, this research used oral monologue test. The researcher used descriptive statistics to analyzed the data that indicated general tendencies in the data (range, mean, and median).  Based on the data found that the students got minimum score was 45, maximum score was 82, range score was 37 and mean score 63.75.  In this case, the students’ speaking English ability on specific purpose of learning were on the good level. It can be concluded that the students were able to speak English on specific purpose of learning